2020
DOI: 10.1097/mjt.0000000000001159
|View full text |Cite
|
Sign up to set email alerts
|

Transient Psychosis After Low-Dose Pregabalin Discontinuation

Abstract: GABAergic activity, such as pregabalin, support this hypothesis. 6 It is a known fact that pregabalin should be used carefully because it has the potential for addiction and abuse. Our report suggests that clinicians should be aware that pregabalin may cause psychotic disorders if not discontinued gradually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It is also important to consider the duration of pregabalin use. Case 1 showed pregabalin withdrawal after only 2 months of pregabalin use, and previous reports have also shown pregabalin withdrawal in cases after a few weeks or 45 days of short‐term pregabalin use 8,11 . Case 1 was particularly worth reporting because it suggested that even a short period of a regular dose of pregabalin can cause physical dependence.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is also important to consider the duration of pregabalin use. Case 1 showed pregabalin withdrawal after only 2 months of pregabalin use, and previous reports have also shown pregabalin withdrawal in cases after a few weeks or 45 days of short‐term pregabalin use 8,11 . Case 1 was particularly worth reporting because it suggested that even a short period of a regular dose of pregabalin can cause physical dependence.…”
Section: Discussionmentioning
confidence: 74%
“…We identified 463 articles through the systematic literature search. Of these, six case reports (six cases) were identified in which withdrawal symptoms occurred in patients administered pregabalin at the usual dose of 600 mg/d or lower 8‐13 . Table 1 shows the demographic data and clinical symptoms of the six cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One case study presents a 30-year-old female university graduate student with no history of substance abuse treated with 150 mg pregabalin/day because of diffuse body pain 8 . After abrupt discontinuation, she was admitted to the emergency department with a pregabalin withdrawal-associated psychotic episode.…”
Section: Resultsmentioning
confidence: 99%
“…Pregabalin causes a change in dopamine in the central nervous system, which causes a rewarding effect like in many other drugs of abuse 15 . This could also explain why pregabalin and gabapentin are often co-ingested with other drugs, as a synergistic effect occurs and the ‘high’ is potentiated as described in many studies 6–10,12,13 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation